PROMOTION OF STUDENTS FOR ENVIRONMENT FRIENDLY TREE PLANTATION - Jain, Paras; Malaiya, Soman (International Journal of Research -GRANTHAALAYAH, 2017)
Plantation is best way to save environment. Awareness in this connection is important and efforts required creating in mass. Focus of students for promotion of plantation is needed to make regular activity of school. Present study is focused on finding of ways to promote tree plantation and impact of such way on students.